Self-templated synthesis of uniform hollow spheres based on highly conjugated three-dimensional covalent organic frameworks - Liu, Yuan-Yuan; Li, Xiang-Chun; Wang, Shi; Cheng, Tao; Yang, Huiyan; Liu, Chen; Gong, Yanting; Lai, Wen-Yong; Huang, Wei (Nature communications, 2020)
Covalent organic frameworks (COFs) have served as a family of porous crystalline molecules for various promising applications. However, controllable synthesis of COFs with uniform morphology is paramount yet still remains quite challenging. Herein, we report self-templated synthesis of uniform and unique hollow spheres based on highly conjugated three-dimensional (3D) COFs with diameters of 500–700 nm. A detailed time-dependent study reveals the continuous transformation from initial nano sphere-like particles into uniform hollow spherical structures with Ostwald ripening mechanism. Particularly, the resulting 3D COF (3D-Sp-COF) is prone to transport ions more efficiently and the lithium-ion transference number ( t + ) of 3D-Sp-COF reaches 0.7, which even overwhelms most typical PEO-based polymer electrolytes. Inspiringly, the hollow spherical structures show enhanced capacitance performance with a specific capacitance of 251 F g −1 at 0.5 A g −1 , which compares favorably with the vast majority of two-dimensional COFs and other porous electrode materials. Covalent organic frameworks (COFs) are promising porous crystalline materials but controllable synthesis of COFs with uniform morphology remains challenging. Here, the authors report a self-templated synthesis of uniform and unique hollow spheres based on highly conjugated three-dimensional COFs.